2018
DOI: 10.1186/s12891-018-1963-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of platelet-rich plasma in treatment of carpal tunnel syndrome; a randomized controlled trial

Abstract: BackgroundCarpal tunnel syndrome is the most common peripheral entrapment neuropathy, for which conservative treatments are the first measures taken. However, these measures are not usually sufficient. Recently major attention has been drawn to platelet-rich plasma for its possible effects on axon regeneration and neurological recovery. Although few studies have evaluated the effects of this treatment in carpal tunnel syndrome, further investigation is required to reach concrete conclusion.MethodsIn this rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 31 publications
7
78
1
Order By: Relevance
“…Regenerative injections may cause a rapid decrease of symptom severity; however, functional improvement still depends on the recovery of muscle endurance and strength, which requires adequate rest and proper wrist positioning, with the use of a splint. Further, although PRP injection ranked second in effectiveness in terms of functional improvement, the patients in the two included PRP studies [23,29] had additional splinting after the injection. An earlier randomized controlled trial has revealed that splinting combined with corticosteroid injection was superior to corticosteroid injection alone, in terms of functional recovery and symptom relief in CTS [48].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regenerative injections may cause a rapid decrease of symptom severity; however, functional improvement still depends on the recovery of muscle endurance and strength, which requires adequate rest and proper wrist positioning, with the use of a splint. Further, although PRP injection ranked second in effectiveness in terms of functional improvement, the patients in the two included PRP studies [23,29] had additional splinting after the injection. An earlier randomized controlled trial has revealed that splinting combined with corticosteroid injection was superior to corticosteroid injection alone, in terms of functional recovery and symptom relief in CTS [48].…”
Section: Discussionmentioning
confidence: 99%
“…The maximal follow-up duration was 24 weeks in five trials [22,[31][32][33][34], 12 weeks in three trials [27,28,30], 10 weeks in one trial [29], and four weeks in one trial [23]. Only one study [29] reported some minor adverse effects after the injection.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations